Theoretical development of new class Phase Transfer Catalysts - Iribarren, Iñigo (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2024)
This thesis stems from the imperative need to integrate computational chemistry into the pro- cess of designing asymmetric organocatalysts. Traditionally, computational chemistry has been employed as a retrospective tool to analyse results rather than in a prospective manner for predicting results and leading the rational designing process. With this goal in mind, the thesis aims to develop computational strategies that leverage the predictive potential of computational chemistry, thereby initiating a paradigm shift in catalyst design. Organised into five chapters, the thesis tackles various aspects of this approach, addressing and resolving key challenges in catalyst design. The first chapter analysed the most popular conformational analysis software packages, iden- tifying their strengths and weaknesses. The efficiency of each package in different facets of the conformational analysis process is evaluated using five established criteria. A comprehensive list of pros and cons is presented to facilitate the selection of the most suitable software. In the second chapter, the nature of ion-pair interactions is reevaluated. The study examines different models and systems typically grouped under the same category. Three intermediate categories between the pure ion-pair and the hydrogen bond were identified and analysed; namely long-range ion-pair, hydrogen-bond-assisted ion-pair and charge-assisted hydrogen bond. Chapter three investigates the different interaction positions of a cinchona-based catalyst with different anions, providing a binding mode for these complexes. Additionally, three different cyanation reactions are studied, modifying the catalysts to improve the selectivity of the process. Chapter four integrates all previously studied methodologies to examine the asymmetric production of protected amino acids. Collaborating with experimental colleagues, the chapter highlights the importance of rational design in improving catalyst selectivity. This is achieved by strategically introducing a second anchorage point and validating computational analysis conclusions through experimental verification. The final chapter of this thesis introduces a new automatic workflow designed for the accurate description of the transition states involved in a reaction with flexible organic molecules. This innovative workflow seeks to study the reaction steps in an unbiased and more detailed manner, aligning closely with the experimental results compared to manually generated transition states. This research work combined the design of computational strategies and the re-evaluation of basic chemistry concepts to improve the rational design of asymmetric catalysts. It demonstrates the predictive power of computational studies and their ability to guide the design process effectively.
APPROVED
Keywords: asymmetric catalysis; computational chemistry